The Beginnings of Hymnology in a New Guinea Church - Ellenberger, John D. (Practical anthropology, 1962)
The actual steps taken toward the development of Uhunduni hymns are here outlined by Mr. Ellenberger. The combination of Uhunduni patterns of singing with Christian content (as well as some interesting extraneous points) has now become an exercise at which some Uhunduni Christians are quite adept. Uhunduni hymn composition is the culmination of earlier stages of more direct missionary suggestion and direction.